The relationship of fast food, consumption habits, hemoglobin levels, and sleep quality to menstrual cycle - Pibriyanti, Kartika; Alimah, Istiqomah Nurul; Nabawiyah, Hafidhotun; Lutfiya, Lulu'; Mufidah, Indahtul (Alma Ata University Press, 2024)
Background: A health problem that often occurs in adolescent girls is disrupting the menstrual cycle. The prevalence of menstrual cycle disorders has increased from 2012 by 45% to 80% in 2018.Objectives: This study aims to identifying respondent characteristics, determine the relationship between fast food consumption habits, hemoglobin levels and sleep quality on the menstrual cycle. Analyzing which independent variable exerts the most dominant influence on the dependent variable.Methods: This research design used analytical observational quantitative methods with a case-control approach. The sampling technique used uses purposive sampling. Data collection for menstrual cycles using questionnaires and calendars, data on fast food consumption habits were obtained by interviews using FFQ, and hemoglobin level data were obtained by examination using the Easy Touch GC-Hb tool. In contrast, sleep quality data were obtained using PSQI questionnaires. Data were analyzed by Chi-square then continued with multivariate logistic regression analysis.Result: The characteristics of respondents in this study based on age mainly were 19 years old, with 49% in the case group and 44% in the control group. Most respondents have an allowance of Rp.500,000-1,000,000, with the percentage in the case group and control group 51%. The menarche age of respondents in this study was mainly 12 years, with a rate of 37%. The characteristics of respondents in the case and control groups mostly have the same distribution of characteristics based on age 19 years, allowance/mounth of Rp.500,000-1,000,000 and age of menstruation 12 years. The study results showed a relationship between fast food consumption habits on the menstrual cycle (p-value= 0.002, OR= 4.359) and there was a relationship between hemoglobin levels on the menstrual cycle (p-value= 0.003, OR= 4.308). There was a relationship between sleep quality on the menstrual cycle (p-value= 0.000, OR= 18.519).Conclusions: There was a relationship between fast food consumption habits, hemoglobin levels and sleep quality on the menstrual cycle. Hemoglobin levels are at higher risk of menstrual cycles than fast food consumption habits and sleep quality (p-value= 0.042).